An Introduction to the Selected Prevalent Contracts and Products of Islamic Banks - Dr. Hafiz Rao Farhan Ali, (Al Manhal Research Journal, 2023)
Islam is a complete code of life, and its teachings encompass all aspects of lifecycle. One essential aspect of human life is economic activities, and Islamic teachings provide guidance on various economic aspects. Agriculture, trade, industry and labor, all have abundant economic teachings from Islam. In the current era, banking has deep connections with economic activities, rather it should be said that banking is an essential part of economics. Allah has provided a fundamental principle regarding banking, emphasizing that trade is permissible (halal), while usury (riba) is prohibited (haram). This implies that banking based on trade is allowed, but banking activities based on interest are not permitted. Islamic banking industry operates on this principle, incorporating various commercial contracts to develop different products. In this article, a brief introduction of these contracts and products based on them is presented. First, the meaning and understanding of each contract is explained, followed by a discussion of its permissibility in the light of Islamic teachings. Lastly, details are given regarding how Islamic Banking products have been designed on modern techniques in the present era. The article employs a qualitative research methodology, drawing information from various books of Islamic jurisprudence, books on Islamic banking, research papers, and the websites of Islamic banks. The findings suggest that designing products based on various contracts and then conducting Sharia-compliant banking is a commendable effort. It is essential to encourage this movement. However, it is also necessary to ensure maximum Shariah compliance in banking based on these products.